The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Camera trapping for density estimation: comparing the TIFC model to aerial surveys for multiple ungulate populations - Jennifer M. Foca; Darcy R. Visscher; Marcus Becker; Mark S. Boyce (Environmental Monitoring and Assessment, 2025)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

The influence of habitat alteration is widespread, but the impact of climate cannot continue to be discounted - Melanie Dickie; Robert Serrouya; Marcus Becker; Craig DeMars; Michael J. Noonan; Robin Steenweg; Stan Boutin; Adam T. Ford (Global Change Biology, 2024)

Bacterial burden and molecular characterization of Coxiella burnetii in shedding pregnant and postpartum ewes from Saint Kitts - Mayra Trujillo; Anne Conan; Ana Cláudia Calchi; Katja Mertens-Scholz; Anna Becker; Christa Gallagher; Alex Mau; Silvia Marchi; Marcus Machado; Marcos Rogério André; Aspinas Chapwanya; Ananda Müller (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Habitat alteration or climate: What drives the densities of an invading ungulate? - Melanie Dickie; Robert Serrouya; Marcus Becker; Craig DeMars; Michael J. Noonan; Robin Steenweg; Stan Boutin; Adam T. Ford (Global Change Biology, 2024)
Anthropogenic habitat alteration and climate change are two well‐known contributors to biodiversity loss through changes to species distribution and abundance; yet, disentangling the effects of these two factors is often hindered by their inherent confound across both space and time. We leveraged a contrast in habitat alteration associated with the jurisdictional boundary between two Canadian provinces to evaluate the relative effects of spatial variation in habitat alteration and climate on white‐tailed deer ( Odocoileus virginianus ) densities. White‐tailed deer are an invading ungulate across much of North America, whose expansion into Canada's boreal forest is implicated in the decline of boreal caribou ( Rangifer tarandus caribou ), a species listed as Threatened in Canada. We estimated white‐tailed deer densities using 300 remote cameras across 12 replicated 50 km 2 landscapes over 5 years. White‐tailed deer densities were significantly lower in areas where winter severity was higher. For example, predicted deer densities declined from 1.83 to 0.35 deer/km 2 when winter severity increased from the lowest value to the median value. There was a tendency for densities to increase with increasing habitat alteration; however, the magnitude of this effect was approximately half that of climate. Our findings suggest that climate is the primary driver of white‐tailed deer populations; however, understanding the mechanisms underpinning this relationship requires further study of over‐winter survival and fecundity. Long‐term monitoring at the invasion front is needed to evaluate the drivers of abundance over time, particularly given the unpredictability of climate change and increasing prevalence of extreme weather events.

New variant strain of Streptococcus canis with Lancefield group C isolated from canine otitis externa - Miriam Katsburg; Julian Brombach; Dennis Hanke; Etienne Aubry; Antina Lübke-Becker; Marcus Fulde (Veterinary Microbiology, 2023)

MOG-Specific T Cells Lead to Spontaneous EAE with Multilocular B Cell Infiltration in the GF-IL23 Model - Louisa Nitsch; Simon Petzinna; Julian Zimmermann; Daniel R. Getts; Albert Becker; Marcus Müller (NeuroMolecular Medicine, 2022)
Although IL-23 and downstream signal transduction play essential roles in neuroinflammation, the local impact of IL-23 in multiple sclerosis is still not fully understood. Our previous study revealed that the central nervous system (CNS)-restricted expression of IL-23 in a mouse model with astrocyte-specific expression of IL-23, called GF-IL23 mice, leads to spontaneous formation of infiltrates in the brain, especially in the cerebellum. To further investigate the impact of CNS-specific IL-23-expression on neuroinflammation, we studied the GF-IL23 model in mice expressing a myelin oligodendrocyte glycoprotein (MOG)-specific T cell receptor (GF23-2D2 mice). The GF23-2D2 mice developed a chronic progressive experimental autoimmune encephalomyelitis with myelitis and ataxia without requiring additional immunization. CNS-production of IL-23 alone induced pronounced neuroinflammation in the transgenic MOG-specific T cell receptor model. The GF23-2D2 mice spontaneously developed multilocular infiltrates with a high number of B cells, demyelination and a proinflammatory cytokine milieu indicating that the interaction of encephalitogenic T cells and B cells via co-stimulatory factors seemed to be crucial.

Correction to: Local Wnt3a treatment restores bone regeneration in large osseous defects after surgical debridement of osteomyelitis - Johannes Maximilian Wagner; Felix Reinkemeier; Mehran Dadras; Christoph Wallner; Julika Huber; Alexander Sogorski; Maxi Sacher; Sonja Schmidt; Marius Drysch; Stephanie Dittfeld; Mustafa Becerikli; Kathrin Becker; et al. (Journal of Molecular Medicine, 2022)

Local Wnt3a treatment restores bone regeneration in large osseous defects after surgical debridement of osteomyelitis - Johannes Maximilian Wagner; Felix Reinkemeier; Mehran Dadras; Christoph Wallner; Julika Huber; Alexander Sogorski; Maxi Sacher; Sonja Schmidt; Marius Drysch; Stephanie Dittfeld; Mustafa Becerikli; Kathrin Becker; et al. (Journal of Molecular Medicine, 2020)
Impaired bone homeostasis caused by osteomyelitis provokes serious variations in the bone remodeling process, thereby involving multiple inflammatory cytokines to activate bone healing. We have previously established a mouse model for post-traumatic osteomyelitis and studied bone regeneration after sufficient debridement. Moreover, we could further characterize the postinfectious inflammatory state of bony defects after debridement with elevated osteoclasts and decreased bone formation despite the absence of bacteria. In this study, we investigated the positive effects of Wnt-pathway modulation on bone regeneration in our previous established mouse model. This was achieved by local application of Wnt3a, a recombinant activator of the canonical Wnt-pathway. Application of Wnt3a could enhance new bone formation, which was verified by histological and μ-CT analysis. Moreover, histology and western blots revealed enhanced osteoblastogenesis and downregulated osteoclasts in a RANKL-dependent manner. Further analysis of Wnt-pathway showed downregulation after bone infections were reconstituted by application of Wnt3a. Interestingly, Wnt-inhibitory proteins Dickkopf 1 (DKK1), sclerostin, and secreted frizzled protein 1 (sFRP1) were upregulated simultaneously to Wnt-pathway activation, indicating a negative feedback for active form of Beta-catenin. In this study, we could demonstrate enhanced bone formation in defects caused by post-traumatic osteomyelitis after Wnt3a application. Key messages Osteomyelitis decreases bone regeneration Wnt3a restores bone healing after infection Canonical Wnt-pathway activation with negative feedback

CNS-Specific Synthesis of Interleukin 23 Induces a Progressive Cerebellar Ataxia and the Accumulation of Both T and B Cells in the Brain: Characterization of a Novel Transgenic Mouse Model - Louisa Nitsch; Julian Zimmermann; Marius Krauthausen; Markus J. Hofer; Raman Saggu; Gabor C. Petzold; Michael T. Heneka; Daniel R. Getts; Albert Becker; Iain L. Campbell; Marcus Müller (Molecular Neurobiology, 2019)

Nitrogen turnover and greenhouse gas emissions in a tropical alpine ecosystem, Mt. Kilimanjaro, Tanzania - Adrian Gütlein; Marcus Zistl-Schlingmann; Joscha Nico Becker; Natalia Sierra Cornejo; Florian Detsch; Michael Dannenmann; Tim Appelhans; Dietrich Hertel; Yakov Kuzyakov; Ralf Kiese (Plant and Soil, 2017)

Reconstruction of past methane availability in an Arctic Alaska wetland indicates climate influenced methane release during the past ~12,000 years - Matthew J. Wooller; John W. Pohlman; Benjamin V. Gaglioti; Peter Langdon; Miriam Jones; Katey M. Walter Anthony; Kevin W. Becker; Kai-Uwe Hinrichs; Marcus Elvert (Journal of Paleolimnology, 2012)

Exploratory multi-criteria analysis in sustainability impact assessment of forest-wood chains: the example of a regional case study in Baden–Württemberg - Bernhard Wolfslehner; Franka Brüchert; Janine Fischbach; Werner Rammer; Gero Becker; Marcus Lindner; Manfred J. Lexer (European Journal of Forest Research, 2012)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)